Does Postponing Minimum Retirement Age Improve Healthy Behaviours Before Retirement? Evidence from Middle-Aged Italian Workers - Marco Bertoni; Giorgio Brunello; Gianluca Mazzarella (Institute for the Study of Labor (IZA), 2016)
By increasing the residual working horizon of employed individuals, pension reforms that raise minimum retirement age are likely to affect the returns to investments in health-promoting behaviours before retirement, with consequences for individual health. Using the exogenous variation in minimum retirement age induced by a sequence of Italian pension reforms during the 1990s and 2000s, we show that Italian males aged 40 to 49 reacted to the longer time to retirement by raising regular exercise and by reducing smoking and regular alcohol consumption. Dietary habits were also affected, with positive consequences on obesity and self-reported satisfaction with health.
Keywords: H55; I12; J26; 330; retirement; working horizon; healthy behaviours; pension reforms